High levels of exfoliated fragments following glycocalyx destruction in hemorrhagic fever with the renal syndrome are associated with mortality risk - Du, Hong; Hu, Haifeng; Li, Jing; Wang, Xiaoyan; Jiang, Hong; Lian, Jianqi; Zhang, Ying; Wang, Pingzhong (Frontiers in Medicine, 2023)
Background The glycocalyx is a gel-like structure that covers the luminal side of vascular endothelial cells. It plays an important role in maintaining the integrity of the vascular endothelial barrier structure. However, the presence or absence of glycocalyx destruction in hemorrhagic fever with renal syndrome (HFRS) and its specific mechanism and role is still unclear. Methods In this study, we detected the levels of exfoliated glycocalyx fragments, namely, heparan sulfate (HS), hyaluronic acid (HA), and chondroitin sulfate (CS), in HFRS patients and investigated their clinical application value on the evaluation of disease severity and prognosis prediction. Results The expression of exfoliated glycocalyx fragments in plasma was significantly increased during the acute stage of HFRS. The levels of HS, HA, and CS in HFRS patients during the acute stage were significantly higher than in healthy controls and convalescent stages of the same type. HS and CS during the acute stage gradually increased with the aggravation of HFRS, and both fragments showed a significant association with disease severity. In addition, exfoliated glycocalyx fragments (especially HS and CS) showed a significant correlation with conventional laboratory parameters and hospitalization days. High levels of HS and CS during the acute phase were significantly associated with patient mortality and demonstrated an obvious predictive value for the mortality risk of HFRS. Conclusion Glycocalyx destruction and shedding may be closely associated with endothelial hyperpermeability and microvascular leakage in HFRS. The dynamic detection of the exfoliated glycocalyx fragments may be beneficial for the evaluation of disease severity and prognosis prediction in HFRS.